Colloquy with Clifford G. Christians in Urbana-Champaign. Issue 1 (1st January 2016) - Cortes, Robert Z.
Abstract: On 14 September 2015, Clifford G. Christians, one of the world's leading communication ethics scholar, was interviewed by Robert Z. Cortes, a PhD candidate of the Pontifical University of Santa Croce (Rome, Italy), in the campus of the University of Illinois (Urbana-Champaign). This article is an edited version of that interview. The themes covered in this interview span almost the entire range of Christians' scholarship in communication ethics. Responding to straight-from-the-shoulder questions in reciprocally candid fashion, Christians re-affirmed and added nuances to topics he has thoroughly treated in much of his written work: the importance of both theoretical ethics and practical case discussions in a free-standing course in ethics; openness with one's own, and to the other's, worldview and pre-suppositions as the basis of any conversation in ethics; the evolution of communitarianism to communitas ; the necessity and challenges of including religious ethics in the discussion of ethics; the possibilities of achieving a global normative theory for communication ethics. For the first time, Christians comments more directly on his collaboration with some Catholic scholars and compares his idea of 'faith and reason' with that of an influential Catholic thinker.